A Comparative Cross-Sectional Study of Coagulation Profiles and Platelet Parameters of Schistosoma mansoni-Infected Adults at Haik Primary Hospital, Northeast Ethiopia - Bisetegn, Habtye; Feleke, Daniel Getacher; Ebrahim, Hussen; Tesfaye, Melkam; Gedefie, Alemu; Erkihun, Yonas (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Introduction. Schistosoma mansoni is an intravascular parasite that interacts with all components of the host blood. Nearly, 10% of S. mansoni-infected patients progress to severe hepatosplenic Schistosomiasis is characterized by periportal fibrosis, obstruction of intrahepatic veins, presinusoidal portal hypertension, and splenomegaly. Thus, this study aimed to compare the basic coagulation profiles and platelet parameters of S. mansoni-infected adults and noninfected individuals as controls at Haik Primary Hospital, Northeast Ethiopia. Methods. A comparative cross-sectional study was conducted at Haik Primary Hospital from April to June 2021. The diagnosis and intensity of S. mansoni infection was determined using the Kato–Katz technique. The coagulation profiles and platelet parameters were analyzed using coagulation and hematology analyzers. Data were analyzed using SPSS version 26.0. The Kolmogorov–Smirnov and Shapiro–Wilk tests were done to check the distribution of continuous variables. The Mann–Whitney U test was used to compare the coagulation profiles and platelet parameters. Spearman’s rank-order correlation was done to assess the correlation between the intensity of infection and coagulation profiles and platelet parameters. In all comparison, a P value <0.05 was considered statistically significant. Result. In this study, a total of 180 study participants (90 S. mansoni-infected adults and 90 controls) were included. Of the total S. mansoni-infected adults, 55.6%, 28.9%, 33, and 15.6% had light, moderate, and heavy intensity of infections, respectively. All S. mansoni-infected study participants had prolonged prothrombin time (PT) and international normalized ratio (INR). Moreover, about 80% of S. mansoni-infected adults had prolonged activated partial thromboplastin time (APTT). Thrombocytopenia was found in 26.7% of the S. mansoni-infected adults. The Mann–Whitney U test showed a statistically significant difference in coagulation profiles between S. mansoni-infected adults and healthy controls (P-value ≤0.001). The Kruskal–Wallis H-test showed a significant difference in PT, APTT, and INR between the intensity of infection and healthy controls (P-value <0.05). Conclusion. This study showed a prolonged coagulation time in S. mansoni-infected individuals. Thus, screening of schistosomiasis patients for hemostatic abnormalities and treating the underlying disorder is crucial.